1980
DOI: 10.1103/physrevlett.45.1801
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ablatively Imploded Spherical Shells

Abstract: Compression of plasma in laser-driven implosions has been characterized as "ablative" or "exploding pusher" according to the relative importance of surface ablation pressure and bulk pressure due to preheating by electrons. To date, experimental study of ablative implosions has been limited, 1 partly because their high-density low-temperature plasma yields little diagnostic information in the form of x-ray or fusion-product emission compared with exploding-pusher implosions. 2 The development of x-ray probing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Numerous authors have identified that ICF experiments performed at lower convergence ratios can show improved agreement with simulations; a (by no means complete) selection can be found in references [28][29][30][31][32][33][34][35]. Such a trend was evident as far back as 1980 [36] when it was observed that lower initial aspect ratios (thicker shells, and as such lower implosion velocities and lower convergence ratios) resulted in more 1D-like performance; however, the laser energies available at the time made the pursuit of high gain at low convergence ratios unfeasible. This trend was again observed recently in the work performed by Olson et al, looking at indirect drive shots on wetted foam capsules on the NIF [5].…”
Section: (B) Low Convergence Ratiomentioning
confidence: 99%
“…Numerous authors have identified that ICF experiments performed at lower convergence ratios can show improved agreement with simulations; a (by no means complete) selection can be found in references [28][29][30][31][32][33][34][35]. Such a trend was evident as far back as 1980 [36] when it was observed that lower initial aspect ratios (thicker shells, and as such lower implosion velocities and lower convergence ratios) resulted in more 1D-like performance; however, the laser energies available at the time made the pursuit of high gain at low convergence ratios unfeasible. This trend was again observed recently in the work performed by Olson et al, looking at indirect drive shots on wetted foam capsules on the NIF [5].…”
Section: (B) Low Convergence Ratiomentioning
confidence: 99%
“…(1) At the shortest laser wavelengths, there is still some incertitude concerning the scaling versus laser intensity. For instance, measurements at 0.351 mm (Key et al, 1983(Key et al, , 1979 showed a scaling % I 0.3 , very different from what is predicted by theoretical models (usually % I 0.7 ). Such experimental results were dominated by 2D and hot spots effects.…”
Section: Introductionmentioning
confidence: 49%
“…An important contribution to diagnostics was the first use of X-ray back-lighting (or radiographic) techniques for the study of implosions. Two-dimensional pulsed radiography was demonstrated initially [9] and then streak camera imaging was used to show the temporal evolution of compression in one dimension [10]. Interest in compression physics shifted from exploding pushers to ablative compression, and sixbeam experiments at X= 1.05 nm showed degraded compression of high-aspect-ratio shells using streaktime-resolved radiography [10].…”
Section: Implosion Dynamics and Compressionmentioning
confidence: 99%
“…Two-dimensional pulsed radiography was demonstrated initially [9] and then streak camera imaging was used to show the temporal evolution of compression in one dimension [10]. Interest in compression physics shifted from exploding pushers to ablative compression, and sixbeam experiments at X= 1.05 nm showed degraded compression of high-aspect-ratio shells using streaktime-resolved radiography [10]. With six green beams (X = 0.53 Mm), streak radiographic methods showed improvement in drive pressure at the shorter wavelength [11] (Fig.…”
Section: Implosion Dynamics and Compressionmentioning
confidence: 99%